2020
DOI: 10.1007/s11273-019-09694-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water table levels and short-term ditch restoration on mountain peatland carbon cycling in the Cordillera Blanca, Peru

Abstract: I would like to start by thanking my family, my dad and sisters, for their love and support through this whole process. Infinite thanks to Rod Chimner, Erik Lilleskov, and John Hribljan, who shared their knowledge, wisdom, and so many wonderful moments with me. Thank you Molly Cavaleri for being part of the committee and for your inputs to this project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Since the latter two processes make the greatest contribution to the CH 4 flux in peatlands (Whalen, Reeburgh, and Sandbeck 1990;Lai 2009), the changes in peat aeration, compaction and temperature as well as nutrient level and vegetation cover can substantially influence CH 4 emissions (Berger et al 2018). Lowered water levels reduce CH 4 emissions by decreasing the abundance of methanogens and CH 4 production and increasing CH 4 oxidation levels, while raised water levels have a higher potential of anaerobic CH 4 production (Frenzel and Karofeld 2000;Roulet 2000; The relationship of CH 4 flux and peatland flooding is similar in peatlands in different regions as verified by both field observations (Roulet and Moore 1995;Nykanen et al 1998;Bellisario et al 1999;Chimner and Cooper 2003a;Strack, Waddington, and Tuittila 2004;Jauhiainen et al 2005;Strack, Waller, and Waddington 2006b;Myers-Smith et al 2007;Moore et al 2011;Yrjala et al 2011;Blodau and Siems 2012;Ballantyne et al 2014;Chimner et al 2016;Laine et al 2019b;Zhang et al 2019;Planas-Clarke et al 2020) and manipulation experiments (Dise, Gorham, and Verry 1993;Funk et al 1994;Aerts and Ludwig 1997;Blodau, Basiliko, and Moore 2004;Strack and Waddington 2007;Turetsky et al 2008;Chivers et al 2009;Dinsmore et al 2009;Laine et al 2009;Pearson et al 2015;Olefeldt et al 2017;Kang et al 2018;…”
Section: Effects Of Water Level Alteration On Ch 4 Emissionsmentioning
confidence: 82%
See 2 more Smart Citations
“…Since the latter two processes make the greatest contribution to the CH 4 flux in peatlands (Whalen, Reeburgh, and Sandbeck 1990;Lai 2009), the changes in peat aeration, compaction and temperature as well as nutrient level and vegetation cover can substantially influence CH 4 emissions (Berger et al 2018). Lowered water levels reduce CH 4 emissions by decreasing the abundance of methanogens and CH 4 production and increasing CH 4 oxidation levels, while raised water levels have a higher potential of anaerobic CH 4 production (Frenzel and Karofeld 2000;Roulet 2000; The relationship of CH 4 flux and peatland flooding is similar in peatlands in different regions as verified by both field observations (Roulet and Moore 1995;Nykanen et al 1998;Bellisario et al 1999;Chimner and Cooper 2003a;Strack, Waddington, and Tuittila 2004;Jauhiainen et al 2005;Strack, Waller, and Waddington 2006b;Myers-Smith et al 2007;Moore et al 2011;Yrjala et al 2011;Blodau and Siems 2012;Ballantyne et al 2014;Chimner et al 2016;Laine et al 2019b;Zhang et al 2019;Planas-Clarke et al 2020) and manipulation experiments (Dise, Gorham, and Verry 1993;Funk et al 1994;Aerts and Ludwig 1997;Blodau, Basiliko, and Moore 2004;Strack and Waddington 2007;Turetsky et al 2008;Chivers et al 2009;Dinsmore et al 2009;Laine et al 2009;Pearson et al 2015;Olefeldt et al 2017;Kang et al 2018;…”
Section: Effects Of Water Level Alteration On Ch 4 Emissionsmentioning
confidence: 82%
“…Spatial and temporal correlations have been observed between NEE and water table depth in both intact and disturbed peatlands (Jungkunst and Fiedler 2007;Silvola et al 1996;Strack et al, 2014;Helfter et al 2015;Lund et al 2012;McVeigh et al, 2014;Peichl et al 2014;Strachan et al, 2015;Laine et al 2007). Specifically, higher NEE (lower C uptake) corresponded to water table decline induced by drought or drainage (Roulet et al 2007;Yurova et al 2007;Koehler, Sottocornola, and Kiely 2011;Peichl et al 2014;Chimner et al 2016;Olefeldt et al 2017;Laine et al 2019b), while lower NEE was found in restored areas after rewetting compared to drained peatlands (Karki et al 2016;Swenson et al 2019;Planas-Clarke et al 2020). For example, peatland restoration by damming ditches in Colorado mountain fens raised water table from −45 cm to −15 cm, and lowered NEE from −1.28 to −2.19 g CO 2 m −2 h −1 (Schimelpfenig, Cooper, and Chimner 2014).…”
Section: Effects Of Water Level Alteration On Carbon Balancementioning
confidence: 96%
See 1 more Smart Citation
“…Water level management had the greatest positive impact on the sink function of mesocosms under RCP 8.5 followed by RCP 4.5 (Figure 4e) by stimulating the growth of vascular plants (sedges and dwarf shrubs) during the growing season over the 2-year experiment (Figure 5b,c;Beyer et al, 2021). Other studies showed a lower NEE (higher CO 2 uptake) in the restored areas after rewetting compared to drained peatlands (Karki et al, 2016;Planas-Clarke et al, 2020;Schimelpfenig et al, 2014;Swenson et al, 2019). For example, Nugent et al (2018) indicated that internal hydrological controls can strengthen the stability and strong carbon sink function of peatlands during summer drawdowns.…”
Section: Interactive Effect Of Climate Change and Water Level Management On The Co 2 Sink Function Of Managed Mesocosmsmentioning
confidence: 86%
“…While methanogenesis in bogs is largely driven by the hydrogenotrophic (H 2 -CO 2 -dependent) pathway, in fens the acetoclastic (acetate dependent) pathway can be predominant (Horn et al, 2003;Galand et al, 2005). Lowering the water table of peatlands is associated with reduced CH 4 emissions in a diverse range of peat types (Roulet et al, 1993;Zhang et al, 2019;Planas-Clarke et al, 2020). Drainage increases the exposure of peat soil to oxygen which inhibits methanogenesis and favors methanotrophic oxidation of CH 4 (Serrano-Silva et al, 2014); rewetting is expected to have the opposite effect and increase long-term CH 4 emissions from a peatland.…”
Section: Methanogens and Methanotrophsmentioning
confidence: 99%